Digital Payments and Empowering an Inclusive Financial System in India - Husain, Arshia; Daryal, Anjali (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
People in India think that financial inclusion is very important for the country's growth and economic might. But in rural and semi-urban regions, access to traditional banking services has been limited, making it hard for people to get the financial tools they need. Digital payment methods have helped solve this problem and have been very important in making financial services more accessible to everyone. This study seeks to examine the ways in which digital payment platforms, including UPI, mobile wallets, and online banking, are enhancing financial accessibility and influencing economic inclusion in India. The study concluded that digital payments have made transactions faster, more open, and cheaper, which has made it easier for those living in rural and semi-urban areas to use banking services. Also, technology has made it easier to learn about money, keep track of it, and retain records, which has led to more organized financial behavior and choices. This study also demonstrates that government actions, like digitalization drives and financial inclusion plans, enhance the efficacy of digital payments. The results show that digital payment methods are helping to make more people in India financially included, and more growth and new technology will help even more people get involved in the economy.